Interactions between a social movement and residents of the Eliana Silva occupation in the Barreiro region, city of Belo Horizonte - Ferreira, Diego Vales Deslandes; Jayme, Juliana Gonzaga (Pontifícia Universidade Católica de São Paulo, 2019)
This paper intends to contribute to the debate on the constitution of a particular model of informal housing: the “occupations” (in Portuguese, ocupações). The goal is to analyze interactions between residents of the Eliana Silva occupation, located in the Barreiro region in the city of Belo Horizonte, State of Minas Gerais, Brazil, and the social housing movement in the formation of this settlement. To do this, we conducted informal conversations and semistructured interviews with residents, both activists and residents with no ties with the organization. We argue that the settlement represents modes of use and appropriation of the urban space, marked by constant changes due to disputes and negotiations between the occupants’ mobility and the social movements’ and the State’s agenda.